Effects of Social Capital Models on Social Capital Perceptions of Older Adults Living Alone, Social Capital Perceptions, and Satisfaction of Community Network Participation - Pankong, Orawan; Keawyota, Kanokporn; Chaowiang, Kanok-on; Yotkhamlue, Kwanchanok; Sumridpeam, Pornthip (Princess of Naradhiwas University Journal, 2025)
Participatory action research aimed to: 1) investigate the problems, social capital needs, and resources of social capital of older adults living alone; 2) develop a social capital model for older adults living alone; and 3) evaluate the model’s effectiveness. The samples were selected by multi -stage random sampling which consisted of 30 older adults living alone and 30 community networks which included 14 volunteer older adult caregivers, 6 community leaders, 4 health care professionals, and 6 local administrative organization personnels. The research instruments included focus group discussion questionnaires, social capital perceptions of older adult measurement, social capital perceptions of community network measurement, and satisfaction of community network participation measurement. Data were analyzed using descriptive statistics, paired t-test statistics, and content analysis. According to the study’s findings, the social capital model for older adults living alone was created in four stages: 1) identifying the problems and needs of older adults and social capital resources; 2) planning and defining joint roles and responsibilities; 3) implementing the plan; and 4) evaluating the results. Consequently, 1) older adults’ perceptions of social capital after program implementation were statistically significantly higher than their perceptions before program implementation at a statistical level of.05 (t = 3.064, p =.005); 2) the community network’s perceptions of social capital after program implementation were statistically significantly higher than their perceptions before program implementation at a statistical level of.05 (t = -10.562, p =.000); and 3) the satisfaction of community network participation following program implementation was at a high level (x ̅ = 4.29, S.D. =.39).